(untitled) (Physical Sciences and Technology, 2025)
This study focuses on the analysis of underground waters from Khaudak and Uchkizil, located in the south ern region of Uzbekistan. These waters are characterized by the presence of various mineral salts, including iodine-containing compounds. The research examines the similarities between these waters, as well as their compositional changes over time under the influence of external environmental factors. Water samples col lected at different intervals were analyzed to monitor variations in composition. The elemental content of the samples was determined using X-ray fluorescence (XRF) analysis, which revealed that iron compounds present in the water tend to precipitate over time. The initial iron content of the water was approximately 0.130%, with subsequent sedimentation resulting in iron-rich deposits containing up to 65% iron. In addi tion, a freshly collected water sample was treated with specific oxidizing agents for iodine and stored for one month. This process led to the formation of a reddish-brown precipitate primarily composed of iron and chlorine, with minor components including iodine and similar elements. The precipitate was found to contain 1.317% iodine, corresponding to 7.66% (21.32 mg/L) of the total iodine content in the Haudak water. Furthermore, exposure of the water to ultraviolet light under open-air conditions resulted in the oxidation and volatilization of iodine, indicating its sensitivity to photochemical degradation. Key words: Khaudak, Uchkizil, iron (III)-chloride, X-ray fluorescence.